THE IMPACT OF CONSUMER ANIMOSITY ON BOYCOTT INTENTIONS TOWARDS MCDONALD’S: EXAMINING THE INFLUENCE OF COGNITIVE-AFFECTIVE EVALUATION - Elviana, Elviana; Utama, Louis (Graduate Program of Universitas Tarumanagara, 2025)
This study aims to examine the influence of consumer animosity on boycott intention through cognitive judgment and affective evaluation among McDonald's consumers in Indonesia. The sample in this study consists of 120 respondents selected using a purposive sampling technique, with the criteria of being at least 18 years old, boycotting McDonald's, and residing in the Greater Jakarta area. Data was collected through an online questionnaire distributed via social media and processed using statistical analysis with the Structural Equation Modeling (SEM) approach. The results show that consumer animosity has a significant negative effect on cognitive judgment and affective evaluation. Furthermore, cognitive judgment has been proven to have a significant negative effect on boycott intention, while affective evaluation does not significantly impact boycott intention. These findings indicate that consumer animosity plays a crucial role in shaping consumers' rational assessments and boycott behaviors towards McDonald's in Indonesia.